Abdullah b. Avn'ın hadisçiliği ve Basra hadis halkalarıyla ilişkisi - Genel, Salih Zeki (My University, 2023)
İbn Avn Basra’da doğup yetişti ve ilmî hayatının önemli bir bölümünü bu şehirde geçirdi. 85 yıl yaşayarak Emevî ve Abbasî dönemlerine tanıklık etti. Döneminin önde gelen ilim merkezlerine seyahat etti ve buralarda pek çok hocadan istifade ederek elde ettiği rivayet birikimini kendi memleketinde nakletti. Bu çalışmada İbn Avn’ın hadis ilmi ve tarihinin önemli meselelerini içeren birçok konudaki görüşleri, yakın hocaları ve talebeleri, rihleleri, rivayetleri gibi ilmî durum ve konumuna ilişkin muhtelif yönleri incelenmiştir. Bu sayede hicrî II. asırda ilmî yaşantısını sürdüren İbn Avn’ın hadisçi kişiliği, ilmî çevresi, Basra hadis halkalarıyla ilişkileri, şahsî ilgileri ve rivayet birikiminin kimler aracılığıyla daha sonraki nesillere aktarıldığı hakkında bilgi sahibi olunması hedeflenmiştir.

Ibn Avn was born and raised in Basra and spent a significant part of his scientific life there city. He lived 85 years and witnessed the Umayyad and Abbasid periods. He also traveled to the leading scientific centers of his time and transferred the narrations he had obtained by benefiting from many teachers in his hometown. In this study, various aspects of Ibn Avn's scientific status and position, such as his views on many issues including the important issues of hadith science and history, his close teachers and students, his journeys, and the narrations he conveyed were examined. In this way, it is aimed to have information about Ibn Avn's muhaddith personality in Hijri II. century, his scientific environment, his relations with the hadith circles in Basra, his personal interests, and through whom his narration accumulation were transferred to the next generations.
Keywords: Basra; Basra Hadis Halkaları Hadith; Hadis; Hadith; Hadith Circles of Basra; Hicrî II. asır; Hijri II. Century; Ibn Avn; İbn Avn